Menstrual problems among adolescent girls attending at a tertiary care hospital in Bangladesh - Pervin, Hasna Hena; Fatema, Kaniz; Chakma, Bidisha; Kazal, Rezaul Karim; Mahmood, Sharmeen; Begum, Kazi Farhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adolescents constitute almost 20% of our population and one-fifth of the world’s total population. However, menstrual disorders are a common concern among adolescent girls, often impacting their physical and emotional well-being. This study aimed to assess the prevalence and causes of menstrual problems among adolescent girls attending a tertiary care hospital (BSMMU) in Bangladesh. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from January 2017 to December 2017. This study included 668 adolescent girls with various menstrual disorders aged 10-19 years who attended the outpatient department of obstetrics and gynecology of our institution. Results: In this study, out of 668 adolescent girls, 418 (62.6%) had some form of menstrual disorder. The most common were menorrhagia (30.38%), oligomenorrhea (26.07%), and amenorrhea (21.76%). Among those with amenorrhea, 3.58% and 18.18% had primary and secondary amenorrhea respectively. Abnormal uterine bleeding (47.4%) and polycystic ovarian disease (PCOD) (44.29%) were the leading causes among 289 individuals with menstrual dysfunction. In cases of primary amenorrhea, the most frequent cause was Müllerian agenesis (60%), followed by imperforate hymen (20%). For secondary amenorrhea, PCOD (77.63%) was the dominant cause, with anemia, emotional disturbances, and premature ovarian failure. Conclusions: The findings show that menorrhagia, oligomenorrhea, and amenorrhea are frequently common menstrual problems among adolescent girls mostly due to abnormal uterine bleeding and PCOD. The study highlights the need for early diagnosis, proper medical intervention, and specialized adolescent gynecology clinics to improve reproductive health outcomes.